1996
DOI: 10.1111/j.1460-9568.1996.tb01609.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Recording of Spontaneous Activities and Nociceptive Responses from Neurons in the Pars Compacta of Substantia Nigra and in the Lateral Habenula

Abstract: Using simultaneous extracellular single-unit recording in the pars compacta of the substantia nigra and in the lateral habenula of rats, 45 pairs of neurons responding to peripheral nociceptive stimulation were recorded. In 41 of these pairs, nigral dopaminergic neurons were inhibited by peripheral nociceptive stimulation, while lateral habenula neurons were excited. Moreover, in 14 pairs, when sweeps were triggered randomly by spontaneous spikes from lateral habenula neurons the spontaneous firing rate of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 21 publications
3
46
0
1
Order By: Relevance
“…Together, these results suggest that the habenula may play a more active and central role in the long-term modification of monoamine transmission and behavioral responses subsequent to aversive and stressful events. Electrophysiological and c-fos immunoreactivity studies in rodents have indeed demonstrated that the habenula is activated in response to various aversive stressors, including stimulation of the tail, restraint, novel environments, and footshock (Benabid and Jeaugey, 1989;Wirtshafter et al, 1994;Gao et al, 1996;Smith et al, 1997). We have previously reported that the habenula also showed increased expression of synaptic plasticity genes associated with long-term changes in neuronal activity in response to stress associated with fear conditioning (Ressler et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Together, these results suggest that the habenula may play a more active and central role in the long-term modification of monoamine transmission and behavioral responses subsequent to aversive and stressful events. Electrophysiological and c-fos immunoreactivity studies in rodents have indeed demonstrated that the habenula is activated in response to various aversive stressors, including stimulation of the tail, restraint, novel environments, and footshock (Benabid and Jeaugey, 1989;Wirtshafter et al, 1994;Gao et al, 1996;Smith et al, 1997). We have previously reported that the habenula also showed increased expression of synaptic plasticity genes associated with long-term changes in neuronal activity in response to stress associated with fear conditioning (Ressler et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Habenula is an ancient dorsal thalamic structure conserved in vertebrates (Sutherland, 1982). Neurons in habenula are tuned to visual, olfactory, and nociceptive pain inputs (Dreosti et al, 2014;Gao et al, 1996;Jetti et al, 2014). Importantly, habenula is a hub connecting the forebrain limbic system to the brain stem monoaminergic neurons (Hikosaka, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rewardrelated stimuli can take any form, potentially requiring the full processing power of the sensory systems to discriminate them. The fact that the DA signal can be pre-saccadic suggests that rather than a specific role in reward, the response is more consistent with a system which signals a 'sensory predication error' (signalling for example that something salient or important but unpredicated has happened; Redgrave et al, 2011), thus incorporating those studies which have found phasic excitatory responses of DA neurons to novel (Ljungberg et al, 1992), intense (Horvitz et al, 1997) and noxious stimuli (Gao et al, 1996), i.e. stimuli which are not clearly rewarding.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…Phasic responses in DA neurons to noxious stimuli are of course possible. However, these responses -which tend to be short-latency (<100 ms) -only seem to occur when the inducing stimulus itself is of short duration (see Tsai et al, 1980;Hommer and Bunney, 1980;Kelland et al, 1993;Gao et al, 1996;Coizet et al, 2006; however see Mileykovskiy and Morales, 2011).…”
Section: Tonic Changes In Da Cell Activity In Response To Non-noxiousmentioning
confidence: 99%